A relação entre as estratégias de precificação e o desempenho das empresas - Saciloto, Evandro Busata (My University, 2015)
The price is one of the main aspects when costumers are choosing products. Factors such as a higher level of differentiation of products, technological developments and globalization of the economy increased the importance of price, because it is a key element in order to reach the sales amount desired as well as for having an impact in the profitability of the companies. Furthermore, the pricing strategies are paramount for a suitable market positioning consolidation. Therefore, this paper has analysed the strategies and the processes of pricing of 153 companies that are part of the Sindicato das Indústrias Metalúrgicas e de Material Elétrico de Caxias do Sul (SIMECS), verifying the relationship between pricing decision make and their performance. As for the research method, a survey was conducted with a quantitative approach and descriptive study with the persons responsible for the pricing process in their respective enterprises. The analysis of the results used the Factor Analysis, Variance Analysys (ANOVA) and Cluster Analysis. The main results suggest that enterprises tend to consider as a main method of pricing definition a cost based method. However, there are differences in the price strategies and performance verified in different fields of economic activity as well as in the size of the companies researched, defined by the segregation in the three different groups of companies in which the Cluster 1 concentrates the companies of lower performance and smaller size and the other Cluster concentrate the companies of superior performance. Moreover, the data suggest that companies that manage to better understand the perceived value of the customers, allied to strategies of higher prices present an improved performance when compared to their main competitors.
O preço é um dos principais aspectos determinantes para a escolha dos produtos pelos compradores. Fatores como maior diferenciação dos produtos, desenvolvimentos tecnológicos e globalização da economia fizerem com que o preço ganhasse importância, pois é um dos elementos chave para alcançar o volume de vendas desejado e por impactar nos lucros e na rentabilidade das empresas. Além disso, as estratégias de precificação são fundamentais para a consolidação de um posicionamento de mercado adequado. Sendo assim, este trabalho analisou as estratégias e os processos de precificação utilizados em 153 empresas afiliadas ao Sindicato das Indústrias Metalúrgicas e de Material Elétrico de Caxias do Sul (SIMECS), verificando a relação das decisões de preço com o desempenho destas empresas. Como método de pesquisa, foi realizada uma pesquisa quantitativo-descritiva do tipo survey com os responsáveis pelo processo de precificação destas empresas. Para a análise dos resultados, foi empregada a Análise Fatorial a Análise de Variância (ANOVA) e Análise de Cluster Os principais resultados sugerem que as empresas tendem a considerar como principal método de definição de preços o preço baseado em custos. No entanto, existem diferenças entre as estratégias de preços utilizadas e diferenças nos desempenhos apresentados entre os ramos de atividade, bem como no porte das empresas pesquisadas, definido pela separação em três grupos de empresas ou clusters sendo que o Cluster concentra as empresas de menor porte com menor desempenho e os demais Clusters com um desempenho superior. Além disso, os dados sugerem que empresas que pertencem ao Cluster 2 e ao Cluster que conseguem captar melhor o valor percebido dos clientes, aliado a uma estratégia de preços altos, apresentam um melhor desempenho diante dos seus principais concorrentes.
Keywords: Preços - Determinação; Administração de empresas; Basing-point system; Industrial management